A fabrication process for a porous biphase calcium phosphate ceramic scaffold

By adopting specific components and process designs in the preparation process of porous calcium phosphate ceramic scaffolds, the problems of poor mechanical properties and poor osteogenic activity of existing materials are solved, and ceramic scaffolds with high porosity, good pore penetration and high biological activity are prepared, which are suitable for a variety of application environments.

CN119191872BActive Publication Date: 2025-05-02JIANGSU TRAUSIM MEDICAL INSTR
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411342014.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-05-02
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

The existing porous calcium phosphate ceramic stent materials have problems such as poor mechanical properties, poor osteogenic activity, and insufficient single components and biological functions.

Method used

Through the composition and process design in the preparation process, BCP precursor powder, sodium dodecyl sulfate, sodium carboxymethylcellulose and hydrogen peroxide are used, and microwave heating, gradient heating sintering and other processes are used to prepare porous biphasic calcium phosphate ceramic scaffolds with high porosity and good pore penetration, and the BCP precursor powder is modified to improve antibacterial and biological activity.

Benefits of technology

The preparation of porous biphasic calcium phosphate ceramic scaffolds with simple process, high porosity, good pore penetration and high biological activity is achieved, which improves the mechanical properties and osteogenesis induction of the material, and is suitable for applications in bacterial environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191872B_ABST
    Figure CN119191872B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic brackets, and in particular to a preparation process of a novel porous biphasic calcium phosphate ceramic bracket. The invention adopts BCP precursor powder as a raw material, hydrogen peroxide as a foaming agent, sodium carboxymethyl cellulose as a rheological agent, and sodium dodecyl sulfate as a dispersant to prepare calcium phosphate ceramics with high porosity and good pore penetration without using a template through component limitation; the BCP precursor powder is modified, nano zinc oxide is in situ grown on the BCP precursor powder by a microwave hydrothermal method, a styrene-maleic anhydride polymer with a coupling function is grafted, and then a linear polyetheramine is grafted to obtain a modified BCP precursor powder, thereby greatly improving various properties of the ceramic bracket.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ceramic stents, in particular to a preparation process of a novel porous biphasic calcium phosphate ceramic stent. Background Art

[0002] The composition of biphasic calcium phosphate is similar to the inorganic matter of natural bone. Its properties such as biodegradability, absorption and high bioactivity make it an ideal hard tissue replacement material. It is widely used in many fields such as bone replacement, drug sustained release, tissue engineering scaffolds, etc.

[0003] According to the pore-forming principle, the current preparation of porous calcium phosphate ceramics mainly includes three methods: adding pore-forming agents, organic foam impregnation, and gas foaming. However, the current bioceramic scaffold materials still have problems such as poor mechanical properties, poor osteogenic activity, single composition, and biological function. Summary of the Invention

[0004] The purpose of the present invention is to provide a novel preparation process of a porous biphasic calcium phosphate ceramic scaffold to solve the problems raised in the prior art.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A novel porous biphasic calcium phosphate ceramic scaffold preparation process comprises the following steps: mixing BCP precursor powder and sodium lauryl sulfate, adding pure water and hydrogen peroxide and stirring, then adding a dispersant and sodium carboxymethyl cellulose, stirring, microwave heating, drying, gradient temperature sintering, and cooling to obtain a novel porous biphasic calcium phosphate ceramic scaffold.

[0007] Furthermore, the raw material composition of the ceramic scaffold is as follows, by weight: 8-12 parts of BCP precursor powder, 2-7 parts of sodium lauryl sulfate, 0.1-0.8 parts of sodium carboxymethyl cellulose, 0-0.6 parts of dispersant, 3-10 parts of pure water, and 5-12 parts of hydrogen peroxide.

[0008] Furthermore, the working conditions of microwave heating are: microwave treatment at a power of 600 W for 0.5-3 min.

[0009] Furthermore, the working conditions for drying are: keeping warm at 50-100°C for 10-24 hours; the working conditions for gradient temperature sintering are: heating to 230-360°C and keeping warm for 0.5-2 hours, then heating to 1000-1500°C and keeping warm for 1-5 hours, and cooling to 200-300°C and keeping warm for 1-2 hours.

[0010] Furthermore, the preparation of BCP precursor powder includes the following steps: dissolving calcium nitrate in pure water, adjusting the pH to 7-12, adding a mixture of diammonium hydrogen phosphate and pure water, stirring for 1-5 hours, aging, centrifuging, washing, drying, sintering, and grinding to obtain BCP precursor powder.

[0011] Furthermore, the working conditions for aging are: temperature of 10-60° C., time of 12-24 hours; the working conditions for sintering are: temperature of 1100° C.-1300° C., time of 1-6 hours.

[0012] Furthermore, the dispersant is one of sodium lauryl sulfate, polyoxyethylene lauryl ether, and sodium hexametaphosphate.

[0013] Furthermore, the BCP precursor powder is modified to obtain a modified BCP precursor powder, and the preparation of the modified BCP precursor powder comprises the following steps:

[0014] 1) Mix zinc nitrate hexahydrate and deionized water, add BCP precursor powder, add a mixture of triethanolamine aqueous solution and anhydrous ethanol, stir for 1-2 hours, transfer to a reactor, heat to 178-182°C using a 600W microwave digester, and keep warm for 15-20 minutes. Cool, centrifuge, wash, dry, and grind to obtain a composite BCP precursor powder;

[0015] 2) N,N-dimethylformamide and composite BCP precursor powder are mixed, ultrasonically stirred for 1-2 hours, a mixture of styrene-maleic anhydride polymer with coupling function and deionized water is added, ultrasonically shaken for 10-20 minutes, centrifuged, and dried to obtain an intermediate preparation;

[0016] 3) The intermediate preparation and N-methylpyrrolidone are mixed, linear polyetheramine is added, the temperature is raised to 178-182° C. and kept warm for 1-2 hours, deionized water is added, and the mixture is distilled under reduced pressure and dried to obtain a modified BCP precursor powder.

[0017] Furthermore, the preparation of the styrene-maleic anhydride polymer having a coupling function comprises the following steps:

[0018] Under a nitrogen atmosphere, maleic anhydride and toluene are mixed, heated to 72-78°C, a mixed solution of azobisisobutyronitrile and toluene is added, and a mixed solution of styrene, vinyltriethoxysilane and anhydrous ethanol is added. The mixture is kept warm for 30-40 minutes, heated to 83-87°C and kept warm for 50-70 minutes, cooled, filtered, washed and dried to obtain a styrene-maleic anhydride polymer with coupling function.

[0019] Furthermore, the preparation of the linear polyetheramine comprises the following steps:

[0020] Under nitrogen atmosphere, N,N-dimethylethylenediamine and anhydrous ethanol were mixed, and a mixture of 1,4-butanediol diglycidyl ether and anhydrous ethanol was added in an ice bath. The temperature was raised to 38-42°C and kept warm for 22-24 hours. The product was rotary evaporated, precipitated with n-hexane, and dried to obtain a linear polyetheramine.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The present invention provides a novel preparation process for a porous biphasic calcium phosphate ceramic scaffold. Through component and process design, a biphasic calcium phosphate ceramic scaffold with simple process, high porosity, good pore penetration, mass production and good biological activity is prepared.

[0023] The present invention is limited in ingredients, uses BCP precursor powder as a raw material, hydrogen peroxide as a foaming agent, sodium carboxymethyl cellulose as a rheological agent, and sodium lauryl sulfate as a dispersant, and prepares calcium phosphate ceramics with high porosity and good pore penetration without using a template.

[0024] In order to further improve the osteogenic inductivity and mechanical properties of ceramic scaffolds, the BCP precursor powder was modified. Zinc nitrate hexahydrate and triethanolamine were used as raw materials, and nano-zinc oxide was in situ grown on the BCP precursor powder by microwave hydrothermal method to obtain a composite BCP precursor powder, thereby improving the antibacterial properties of the ceramic scaffold and enhancing the applicability of the material in a bacterial environment. Styrene-maleic anhydride polymer with coupling function was prepared by free radical polymerization of maleic anhydride, styrene, and vinyltriethoxysilane, and then the composite BCP precursor powder was treated to obtain an intermediate preparation, in which the introduction of silicon element synergistically with zinc element to enhance the biological activity of the material and promote bone tissue growth. The surface of the composite BCP precursor powder was modified to significantly increase the surface roughness and retention force.

[0025] In order to improve the uniformity of the dispersion of BCP precursor powder in ceramic scaffolds and improve the uniformity of the properties of ceramic scaffolds, so that they can achieve the purpose of uniform superdispersion without the addition of additional superdispersants, the excellent anchoring group and reactivity of polyetheramines are utilized. N,N-dimethylethylenediamine and 1,4-butanediol diglycidyl ether are used as raw materials to synthesize linear polyetheramines with tertiary amines as anchoring groups. The linear polyetheramines are then grafted with intermediate preparations to obtain modified BCP precursor powders. This makes the BCP precursor powder inherently superdispersible, greatly improving the various properties of the ceramic scaffolds. 附图说明

[0026] Figure 1 is a picture of the porous dual-phase calcium phosphate ceramic prepared in Example 1 after sintering;

[0027] Figure 2is a scanning electron microscope ×100 image of the porous dual-phase calcium phosphate ceramic prepared in Example 1;

[0028] Figure 3 is a scanning electron microscope ×250 image of the porous dual-phase calcium phosphate ceramic prepared in Example 1;

[0029] Figure 4 is a scanning electron microscope ×100 image of Comparative Example 1;

[0030] Figure 5 This is a scanning electron microscope ×250 image of Comparative Example 1. DETAILED DESCRIPTION

[0031] The following will clearly and completely describe the technical solutions of the present invention in conjunction with the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without making any creative efforts shall fall within the scope of protection of the present invention.

[0032] It should be noted that if the embodiments of the present invention involve directional indications such as up, down, left, right, front, and back, such directional indications are only used to explain a specific posture, such as the relative position relationship between components, the movement status, etc. If the specific posture changes, the directional indication will also change accordingly. In addition, the technical solutions between the various embodiments may be combined with each other, but they must be based on the premise that they can be implemented by ordinary technicians in this field. If the combination of technical solutions is mutually inconsistent or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection claimed by the present invention.

[0033] The technical solutions of the present invention are further described in detail below with reference to specific embodiments. It should be understood that the following embodiments are merely used to explain the present invention and are not intended to limit the present invention.

[0034] Example 1: A process for preparing a novel porous biphasic calcium phosphate ceramic scaffold comprises the following steps: mixing BCP precursor powder and sodium lauryl sulfate, adding pure water and hydrogen peroxide and stirring, then adding a dispersant and sodium carboxymethyl cellulose, stirring, microwave heating, drying, gradient temperature sintering, and cooling to obtain a novel porous biphasic calcium phosphate ceramic scaffold;

[0035] The raw material composition of the ceramic scaffold is as follows: 9 parts of BCP precursor powder, 6 parts of sodium lauryl sulfate, 0.3 parts of sodium carboxymethyl cellulose, 0.5 parts of dispersant, 6 parts of pure water, and 9 parts of hydrogen peroxide.

[0036] The working conditions of microwave heating were as follows: microwave power of 600 W for 3 min;

[0037] The working conditions for drying are: keeping the temperature at 80℃ for 18h; the working conditions for gradient temperature sintering are: heating to 260℃ and keeping the temperature for 1h, then heating to 1200℃ and keeping the temperature for 1h, and cooling to 300℃ and keeping the temperature for 1h;

[0038] The preparation of BCP precursor powder includes the following steps: dissolving 236.15 g of calcium nitrate in 1000 mL of pure water, adjusting the pH to 10, adding a mixture of 81.5 g of diammonium hydrogen phosphate and 617 mL of pure water, stirring for 3 h, aging, centrifuging, washing, drying, sintering, and grinding to obtain BCP precursor powder;

[0039] The working conditions for aging are: temperature of 40° C. and time of 18 hours; the working conditions for sintering are: temperature of 1200° C. and time of 3 hours; and the dispersant is sodium lauryl sulfate.

[0040] Example 2: A process for preparing a novel porous biphasic calcium phosphate ceramic scaffold, comprising the following steps: mixing BCP precursor powder and sodium lauryl sulfate, adding pure water and hydrogen peroxide and stirring, then adding sodium carboxymethyl cellulose, stirring, microwave heating, drying, gradient temperature sintering, and cooling to obtain a novel porous biphasic calcium phosphate ceramic scaffold;

[0041] The raw material composition of the ceramic scaffold is as follows: 8 parts of BCP precursor powder, 2 parts of sodium lauryl sulfate, 0.1 parts of sodium carboxymethyl cellulose, 3 parts of pure water, and 5 parts of hydrogen peroxide.

[0042] The working conditions of microwave heating were as follows: microwave power of 600 W for 0.5 min;

[0043] The working conditions for drying are: keeping at 50℃ for 24h; the working conditions for gradient temperature sintering are: heating to 230℃ and keeping for 2h, then heating to 1000℃ and keeping for 5h, then cooling to 200℃ and keeping for 2h;

[0044] The preparation of BCP precursor powder includes the following steps: dissolving 236.15 g of calcium nitrate in 1000 mL of pure water, adjusting the pH to 7, adding a mixture of 81.5 g of diammonium hydrogen phosphate and 617 mL of pure water, stirring for 1 hour, aging, centrifuging, washing, drying, sintering, and grinding to obtain BCP precursor powder;

[0045] The working conditions for aging are: temperature 10℃, time 24h; the working conditions for sintering are: temperature 1100℃, time 6h;

[0046] The BCP precursor powder is modified to obtain a modified BCP precursor powder. The preparation of the modified BCP precursor powder comprises the following steps:

[0047] 1) 3 mmol of zinc nitrate hexahydrate and 100 mL of deionized water were mixed, 1.2 g of BCP precursor powder was added, and a mixture of 50 mL of 0.12 mol / L triethanolamine aqueous solution and 80 mL of anhydrous ethanol was added. The mixture was stirred for 1 h, transferred to a reactor, heated to 178°C using a 600 W microwave digester, and kept warm for 20 min. The mixture was cooled, centrifuged, washed, dried, and ground to obtain a composite BCP precursor powder.

[0048] 2) Mix 25 mL of N,N-dimethylformamide and 0.8 g of composite BCP precursor powder, stir ultrasonically for 1 hour, add 1.4 g of styrene-maleic anhydride polymer with coupling function and 25 mL of deionized water, ultrasonically shake for 10 minutes, centrifuge, and dry to obtain an intermediate preparation;

[0049] 3) 8.1 g of the intermediate preparation and 12 mL of N-methylpyrrolidone were mixed, 3.6 g of linear polyetheramine was added, the temperature was raised to 178°C and kept warm for 2 h, 100 mL of deionized water was added, and the mixture was distilled under reduced pressure and dried for 12 h to obtain a modified BCP precursor powder;

[0050] The preparation of the styrene-maleic anhydride polymer with coupling function comprises the following steps:

[0051] Under a nitrogen atmosphere, 2.5 g of maleic anhydride and 50 mL of toluene were mixed, heated to 72° C., a mixture of 5 mg of azobisisobutyronitrile and 10 mL of toluene was added, and a mixture of 2.7 g of styrene, 0.1 g of vinyltriethoxysilane, and 1.5 mL of anhydrous ethanol was added. The mixture was kept warm for 30 min, heated to 83° C. and kept warm for 50 min, cooled, filtered, washed, and dried to obtain a styrene-maleic anhydride polymer with coupling function.

[0052] The preparation of linear polyetheramine comprises the following steps:

[0053] Under a nitrogen atmosphere, 3.6 g of N,N-dimethylethylenediamine and 10 mL of anhydrous ethanol were mixed, and a mixture of 7.2 g of 1,4-butanediol diglycidyl ether and 20 mL of anhydrous ethanol was added in an ice bath. The temperature was raised to 38°C and kept warm for 24 h. The product was rotary evaporated, precipitated with n-hexane, and dried to obtain a linear polyetheramine.

[0054] Example 3: A process for preparing a novel porous biphasic calcium phosphate ceramic scaffold, comprising the following steps: mixing BCP precursor powder and sodium lauryl sulfate, adding pure water and hydrogen peroxide and stirring, then adding sodium carboxymethyl cellulose, stirring, microwave heating, drying, gradient temperature sintering, and cooling to obtain a novel porous biphasic calcium phosphate ceramic scaffold;

[0055] The raw material composition of the ceramic scaffold is as follows: 9 parts of BCP precursor powder, 6 parts of sodium lauryl sulfate, 0.3 parts of sodium carboxymethyl cellulose, 0.5 parts of dispersant, 6 parts of pure water, and 9 parts of hydrogen peroxide.

[0056] The working conditions of microwave heating were as follows: microwave power of 600 W for 3 min;

[0057] The working conditions for drying are: keeping the temperature at 80℃ for 18h; the working conditions for gradient temperature sintering are: heating to 260℃ and keeping the temperature for 1h, then heating to 1200℃ and keeping the temperature for 1h, and cooling to 300℃ and keeping the temperature for 1h;

[0058] The preparation of BCP precursor powder includes the following steps: dissolving 236.15 g of calcium nitrate in 1000 mL of pure water, adjusting the pH to 10, adding a mixture of 81.5 g of diammonium hydrogen phosphate and 617 mL of pure water, stirring for 3 hours, aging, centrifuging, washing, drying, sintering, and grinding to obtain BCP precursor powder; the aging working conditions are: temperature at 40°C for 18 hours; the sintering working conditions are: temperature at 1200°C for 3 hours;

[0059] The BCP precursor powder is modified to obtain a modified BCP precursor powder. The preparation of the modified BCP precursor powder comprises the following steps:

[0060] 1) 3 mmol of zinc nitrate hexahydrate and 100 mL of deionized water were mixed, 1.2 g of BCP precursor powder was added, and a mixture of 50 mL of 0.12 mol / L triethanolamine aqueous solution and 80 mL of anhydrous ethanol was added. The mixture was stirred for 1.5 h, transferred to a reactor, heated to 180°C using a 600 W microwave digester, and kept warm for 18 min. The mixture was cooled, centrifuged, washed, dried, and ground to obtain a composite BCP precursor powder.

[0061] 2) Mix 25 mL of N,N-dimethylformamide and 0.8 g of composite BCP precursor powder, stir ultrasonically for 1.5 h, add 1.4 g of styrene-maleic anhydride polymer with coupling function and 25 mL of deionized water, ultrasonically shake for 15 min, centrifuge, and dry to obtain an intermediate preparation;

[0062] 3) 8.1 g of the intermediate preparation and 12 mL of N-methylpyrrolidone were mixed, 3.6 g of linear polyetheramine was added, the temperature was raised to 180°C and kept for 1.5 h, 100 mL of deionized water was added, and the mixture was distilled under reduced pressure and dried for 12 h to obtain a modified BCP precursor powder;

[0063] The preparation of the styrene-maleic anhydride polymer with coupling function comprises the following steps:

[0064] Under a nitrogen atmosphere, 2.5 g of maleic anhydride and 50 mL of toluene were mixed, heated to 75° C., a mixture of 5 mg of azobisisobutyronitrile and 10 mL of toluene was added, and a mixture of 2.7 g of styrene, 0.1 g of vinyltriethoxysilane, and 1.5 mL of anhydrous ethanol was added. The mixture was kept warm for 35 min, heated to 85° C. and kept warm for 60 min, cooled, filtered, washed, and dried to obtain a styrene-maleic anhydride polymer with coupling function.

[0065] The preparation of linear polyetheramine comprises the following steps:

[0066] Under a nitrogen atmosphere, 3.6 g of N,N-dimethylethylenediamine and 10 mL of anhydrous ethanol were mixed, and a mixture of 7.2 g of 1,4-butanediol diglycidyl ether and 20 mL of anhydrous ethanol was added in an ice bath. The temperature was raised to 40°C and kept warm for 23 h. The product was rotary evaporated, precipitated with n-hexane, and dried to obtain a linear polyetheramine.

[0067] Example 4: A process for preparing a novel porous biphasic calcium phosphate ceramic scaffold, comprising the following steps: mixing BCP precursor powder and sodium lauryl sulfate, adding pure water and hydrogen peroxide and stirring, then adding sodium carboxymethyl cellulose, stirring, microwave heating, drying, gradient temperature sintering, and cooling to obtain a novel porous biphasic calcium phosphate ceramic scaffold;

[0068] The raw material composition of the ceramic scaffold is as follows: 12 parts of BCP precursor powder, 7 parts of sodium lauryl sulfate, 0.8 parts of sodium carboxymethyl cellulose, 10 parts of pure water, and 12 parts of hydrogen peroxide.

[0069] The working conditions of microwave heating were as follows: microwave power 600 W for 1.5 min;

[0070] The working conditions for drying are: keeping the temperature at 100℃ for 10 hours; the working conditions for gradient temperature sintering are: heating to 360℃ and keeping the temperature for 0.5 hours, then heating to 1500℃ and keeping the temperature for 1 hour, and cooling to 300℃ and keeping the temperature for 1 hour;

[0071] The preparation of BCP precursor powder includes the following steps: dissolving 236.15 g of calcium nitrate in 1000 mL of pure water, adjusting the pH to 12, adding a mixture of 81.5 g of diammonium hydrogen phosphate and 617 mL of pure water, stirring for 5 h, aging, centrifuging, washing, drying, sintering, and grinding to obtain BCP precursor powder;

[0072] The working conditions for aging are: temperature 60℃, time 12h; the working conditions for sintering are: temperature 1300℃, time 1h;

[0073] The BCP precursor powder is modified to obtain a modified BCP precursor powder. The preparation of the modified BCP precursor powder comprises the following steps:

[0074] 1) 3 mmol of zinc nitrate hexahydrate and 100 mL of deionized water were mixed, 1.2 g of BCP precursor powder was added, and a mixture of 50 mL of 0.12 mol / L triethanolamine aqueous solution and 80 mL of anhydrous ethanol was added. The mixture was stirred for 1-2 h, transferred to a reactor, heated to 182°C using a 600 W microwave digester, and kept warm for 15 min. The mixture was cooled, centrifuged, washed, dried, and ground to obtain a composite BCP precursor powder.

[0075] 2) Mix 25 mL of N,N-dimethylformamide and 0.8 g of composite BCP precursor powder, stir ultrasonically for 2 h, add 1.4 g of styrene-maleic anhydride polymer with coupling function and 25 mL of deionized water, ultrasonically shake for 20 min, centrifuge, and dry to obtain an intermediate preparation;

[0076] 3) 8.1 g of the intermediate preparation and 12 mL of N-methylpyrrolidone were mixed, 3.6 g of linear polyetheramine was added, the temperature was raised to 182°C and kept for 1 h, 100 mL of deionized water was added, and the mixture was distilled under reduced pressure and dried for 12 h to obtain a modified BCP precursor powder;

[0077] The preparation of the styrene-maleic anhydride polymer with coupling function comprises the following steps:

[0078] Under a nitrogen atmosphere, 2.5 g of maleic anhydride and 50 mL of toluene were mixed, the temperature was raised to 72-78° C., a mixture of 5 mg of azobisisobutyronitrile and 10 mL of toluene was added, and a mixture of 2.7 g of styrene, 0.1 g of vinyltriethoxysilane, and 1.5 mL of anhydrous ethanol was added, the temperature was kept for 40 min, the temperature was raised to 87° C. and the temperature was kept for 50 min, the mixture was cooled, filtered, washed, and dried to obtain a styrene-maleic anhydride polymer with coupling function;

[0079] The preparation of linear polyetheramine comprises the following steps:

[0080] Under a nitrogen atmosphere, 3.6 g of N,N-dimethylethylenediamine and 10 mL of anhydrous ethanol were mixed, and a mixture of 7.2 g of 1,4-butanediol diglycidyl ether and 20 mL of anhydrous ethanol was added in an ice bath. The temperature was raised to 38°C and kept warm for 24 h. The product was rotary evaporated, precipitated with n-hexane, and dried to obtain a linear polyetheramine.

[0081] Comparative Example 1: Commercially available calcium phosphate ceramics (Suzhou Ding'an BCP ceramics, HA:TCP=70:30, 1-2 mm).

[0082] Comparative Example 2: Taking Example 3 as the control group, the styrene-maleic anhydride polymer with coupling function was replaced with a styrene-maleic anhydride copolymer (Y47209: Shanghai Yuanye Biotechnology Co., Ltd.), and the other processes were normal.

[0083] Comparative Example 3: Example 3 was used as a control group, in which no linear polyetheramine was prepared and other processes were normal.

[0084] Sources of raw materials used (for demonstration purposes only):

[0085] Maleic anhydride 108-31-6: Jinan Jinhao Chemical Co., Ltd.; sodium lauryl sulfate S348686, sodium carboxymethyl cellulose C104984, diammonium hydrogen phosphate A112553, zinc nitrate hexahydrate Z111703, triethanolamine T108151, N,N-dimethylformamide D111999, N-methylpyrrolidone M119668, azobisisobutyronitrile A434183, styrene S110375, vinyltriethoxysilane T103647, N,N-dimethylethylenediamine D105347, 1,4-butanediol diglycidyl ether B109380: Aladdin reagent; hydrogen peroxide (mass concentration 30%), calcium nitrate, anhydrous ethanol, toluene, analytical grade: Sinopharm Group reagent.

[0086] Performance test: The ceramic stents prepared in the examples and comparative examples were tested:

[0087] Porosity: Mercury intrusion porosimetry was used for testing. Biodegradability: Samples were placed in sealed tubes containing simulated body fluid (SBF) (CD090: Shanghai Aiyan Biotechnology Co., Ltd.) at a sample mass to SBF volume ratio of 0.2 g:1 mL. The tubes were incubated at 37°C for 7 days, with the SBF replaced daily. The wet weight of the immersed samples was measured, and the weight loss rate was calculated. The results are shown in Table 1.

[0088] Table 1

[0089]

[0090] The present invention provides a novel preparation process for a porous biphasic calcium phosphate ceramic scaffold. Through component and process design, a biphasic calcium phosphate ceramic scaffold with simple process, high porosity, good pore penetration, mass production and good biological activity is prepared.

[0091] according to Figure 2 、 Figure 3 and Figure 4 、 Figure 5 By comparison, it can be seen that the porosity and permeability of the porous biphasic calcium phosphate ceramic scaffold prepared by the present invention are higher than those on the market.

[0092] By comparing Example 3 with Comparative Example 2, it can be seen that in order to further improve the osteogenic inductivity and mechanical properties of the ceramic scaffold, the BCP precursor powder is modified, and zinc nitrate hexahydrate and triethanolamine are used as raw materials, and nano zinc oxide is in situ grown on the BCP precursor powder by a microwave hydrothermal method to obtain a composite BCP precursor powder, thereby improving the antibacterial property of the ceramic scaffold and enhancing the applicability of the material in a bacterial environment; maleic anhydride, styrene, and vinyltriethoxysilane are used for free radical polymerization to prepare a styrene-maleic anhydride polymer with a coupling function, and then the composite BCP precursor powder is treated to obtain an intermediate preparation, wherein the introduction of silicon element cooperates with zinc element to improve the biological activity of the material and promote bone tissue growth. The surface modification of the composite BCP precursor powder can increase the surface roughness and retention force, greatly improving the mechanical properties of the ceramic scaffold.

[0093] By comparing Example 3 with Comparative Example 3, it can be seen that in order to improve the uniformity of dispersion of the BCP precursor powder in the ceramic scaffold and improve the uniformity of the properties of the ceramic scaffold, so that it can achieve the purpose of uniform super dispersion without the addition of an additional super dispersant, the polyetheramine has excellent anchoring groups and reactivity. The linear polyetheramine with tertiary amine as the anchoring group is synthesized using N,N-dimethylethylenediamine and 1,4-butanediol diglycidyl ether as raw materials, and then the linear polyetheramine is grafted with an intermediate preparation to obtain a modified BCP precursor powder, so that the BCP precursor powder has its own super dispersibility, which greatly improves the various properties of the ceramic scaffold.

[0094] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the invention can be embodied in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as illustrative and non-restrictive, and the scope of the invention is defined by the appended claims, not the foregoing description, and all variations within the meaning and range of equivalents of the claims are intended to be included therein. Any reference sign in a claim should not be construed as limiting the claim to which it relates.

Claims

1. A preparation process of a porous biphasic calcium phosphate ceramic scaffold, characterized in that: The method comprises the following steps: mixing BCP precursor powder and sodium dodecyl sulfate, adding pure water and hydrogen peroxide and stirring, then adding a dispersant and sodium carboxymethyl cellulose, stirring, microwave heating, drying, gradient temperature sintering, and cooling to obtain a porous biphasic calcium phosphate ceramic scaffold; The BCP precursor powder is subjected to modification treatment to obtain a modified BCP precursor powder, wherein the preparation of the modified BCP precursor powder comprises the following steps: 1) Mix zinc nitrate hexahydrate and deionized water, add BCP precursor powder, add a mixture of triethanolamine aqueous solution and anhydrous ethanol, stir for 1-2 hours, transfer to a reactor, heat to 178-182°C with a 600W microwave digester, keep warm for 15-20 minutes, cool, centrifuge, wash, dry, and grind to obtain a composite BCP precursor powder; 2) N,N-dimethylformamide and composite BCP precursor powder are mixed, ultrasonically stirred for 1-2 hours, a mixed solution of styrene-maleic anhydride polymer with coupling function and deionized water is added, ultrasonically shaken for 10-20 minutes, centrifuged, and dried to obtain an intermediate preparation; 3) Mix the intermediate preparation and N-methylpyrrolidone, add linear polyetheramine, heat to 178-182°C and keep warm for 1-2h, add deionized water, distill under reduced pressure, and dry to obtain modified BCP precursor powder; The preparation of the styrene-maleic anhydride polymer with coupling function comprises the following steps: In a nitrogen atmosphere, maleic anhydride and toluene are mixed, the temperature is raised to 72-78° C., a mixed solution of azobisisobutyronitrile and toluene is added, a mixed solution of styrene, vinyltriethoxysilane and anhydrous ethanol is added, the temperature is kept for 30-40 minutes, the temperature is raised to 83-87° C. and the temperature is kept for 50-70 minutes, cooling, filtering, washing and drying to obtain a styrene-maleic anhydride polymer with coupling function; The preparation of the linear polyetheramine comprises the following steps: In a nitrogen atmosphere, N,N-dimethylethylenediamine and anhydrous ethanol are mixed, and a mixture of 1,4-butanediol diglycidyl ether and anhydrous ethanol is added in an ice bath, and the temperature is raised to 38-42°C and kept for 22-24 hours, and then rotary evaporated, precipitated with n-hexane, and dried to obtain a linear polyetheramine.

2. The preparation process of a porous biphasic calcium phosphate ceramic scaffold according to claim 1, characterized in that: The raw material composition of the ceramic support is as follows, by weight: 8-12 parts of BCP precursor powder, 2-7 parts of sodium dodecyl sulfate, 0.1-0.8 parts of sodium carboxymethyl cellulose, 0-0.6 parts of dispersant, 3-10 parts of pure water, and 5-12 parts of hydrogen peroxide.

3. The preparation process of a porous biphasic calcium phosphate ceramic scaffold according to claim 1, characterized in that: The working conditions of microwave heating are: microwave treatment at a power of 600 W for 0.5-3 min.

4. The preparation process of a porous biphasic calcium phosphate ceramic scaffold according to claim 1, characterized in that: The working conditions for drying are: keeping warm at 50-100°C for 10-24h; the working conditions for gradient temperature sintering are: heating to 230-360°C and keeping warm for 0.5-2h, then heating to 1000-1500°C and keeping warm for 1-5h, and cooling to 200-300°C and keeping warm for 1-2h.

5. The preparation process of a porous biphasic calcium phosphate ceramic scaffold according to claim 1, characterized in that: The preparation of BCP precursor powder comprises the following steps: Calcium nitrate is dissolved in pure water, the pH is adjusted to 7-12, a mixture of diammonium hydrogen phosphate and pure water is added, stirred for 1-5 hours, aged, centrifuged, washed, dried, sintered, and ground to obtain BCP precursor powder.

6. The preparation process of a porous biphasic calcium phosphate ceramic scaffold according to claim 5, characterized in that: The working conditions for aging are: temperature of 10-60°C, time of 12-24h; the working conditions for sintering are: temperature of 1100°C-1300°C, time of 1-6h.

7. The preparation process of a porous biphasic calcium phosphate ceramic scaffold according to claim 1, characterized in that: The dispersant is one of sodium lauryl sulfate, polyoxyethylene lauryl ether and sodium hexametaphosphate.

Citation Information

Patent Citations

  • Preparation method for calcium polyphosphate-tricalcium phosphate bone bracket

    CN101716369A

  • Silicon / zinc ion doped biphase calcium phosphate ceramic scaffold and preparation method thereof

    CN114767927A